1991
DOI: 10.1037/0022-3514.60.4.509
|View full text |Cite
|
Sign up to set email alerts
|

The trouble of thinking: Activation and application of stereotypic beliefs.

Abstract: Two studies investigated the effects of cognitive busyness on the activation and application of stereotypes. In Experiment 1, not-busy subjects who were exposed to an Asian target showed evidence of stereotype activation, but busy subjects (who rehearsed an 8-digit number during their exposure) did not. In Experiment 2, cognitive busyness once again inhibited the activation of stereotypes about Asians. However, when stereotype activation was allowed to occur, busy subjects (who performed a visual search task d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

46
941
7
21

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,062 publications
(1,019 citation statements)
references
References 48 publications
46
941
7
21
Order By: Relevance
“…The Spencer et al (1998) finding is especially dramatic in that it showed that self-protective motives (to derogate minority group members in order to enhance one's own self-esteem) are able to overcome conditions of attentional shortage (i.e., memory load) that previous research had shown sufficient to prevent such stereotyping from occurring (Gilbert & Hixon, 1991).…”
mentioning
confidence: 96%
“…The Spencer et al (1998) finding is especially dramatic in that it showed that self-protective motives (to derogate minority group members in order to enhance one's own self-esteem) are able to overcome conditions of attentional shortage (i.e., memory load) that previous research had shown sufficient to prevent such stereotyping from occurring (Gilbert & Hixon, 1991).…”
mentioning
confidence: 96%
“…Individuals use stereotypes in judgments to a greater extent when processing resources are scarce or time pressure is high (e.g., Gilbert & Hixon, 1991;Macrae, Milne, & Bodenhausen, 1994). In contrast, when individuals are motivated to respond without prejudice and they have sufficient cognitive resources, they try to control the influence of stereotypes on judgments (e.g., Neuberg & Fiske, 1987).…”
Section: Stereotype Activation and Stereotype Applicationmentioning
confidence: 99%
“…The extent to which stereotypes are activated depends on a number of factors, such as the prototypicality of the group member (Blair, Judd, Sadler, & Jenkins, 2002;Freeman & Ambady, 2009) and the learning history of the perceiver (Gawronski, Deutsch, Mbirkou, Seibt, & Strack, 2008;Weisbuch, Pauker, & Ambady, 2009). Stereotype activation can be described as a partially automatic process in the sense that it can happen relatively quickly (e.g., Dovidio, Evans, & Tyler, 1986) and outside of awareness (e.g., Wittenbrink, Judd, & Park, 1997), while at the same time it depends on processing goals (e.g., Macrae, Bodenhausen, Milne, Thorn, & Castelli, 1997) as well as processing resources (e.g., Gilbert & Hixon, 1991).…”
Section: Stereotype Activation and Stereotype Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most of the work concerned with this distinction has focused on demonstrating that stereotypic knowledge in general, and racial stereotypes in particular, may in fact be activated effortlessly and influence subsequent judgments unbeknownst to the perceiver (Banaji & Greenwald, 1995;Banaji, Hardin, & Rothman, 1993;Devine, 1989;Fazio, Sanbonmatsu, Powell, & Kardes, 1986;Gaertner & McLaughlin, 1983; D. T. Gilbert & Hixon, 1991;Macrae, Stangor, & Milne, 1994;Perdue & Gurtman, 1990). Much less work exists that directly assesses the relationship between implicit and explicit measures of stereotyping and prejudice.…”
mentioning
confidence: 99%